Panicle Angle is an Important Factor in Tef Lodging Tolerance - Blösch, Regula; Plaza-Wüthrich, Sonia; Barbier de Reuille, Pierre; Weichert, Annett; Routier-Kierzkowska, Anne-Lise; Cannarozzi, Gina; Robinson, Sarah; Tadele, Zerihun (Frontiers in Plant Science, 2020)
TTef [Eragrostis tef (Zucc.) Trotter] is an important crop in the Horn of Africa, particularly in Ethiopia, where it is a staple food for over 60 million people. However, the productivity of tef remains extremely low in part due to its susceptibility to lodging. Lodging is the displacement of the plant from the upright position, and it is exacerbated by rain, wind and the application of fertilizer. In order to address the issue of global food security, especially in the Horn of Africa, greater insight into the causes of tef lodging is needed. In this study, we combine modelling and biomechanical measurements to compare the properties relating to lodging tolerance in high yielding, improved tef genotypes, and lower yielding natural landraces. Our results indicate that the angle of the panicle contributes to the likelihood of lodging in tef. Varieties with compact panicles and reduced height had increased lodging resistance compared to the other varieties. By comparing different varieties, we found that overall, the landraces of tef lodged less than improved varieties. We constructed a model of stem bending and found that panicle angle was an important determinant of the amount of lodging. The findings from this study provide key information to those involved in tef improvement, especially those interested in lodging tolerance.